Occupational therapy for older people - Pozzi, Christian; Lanzoni, Alessandro; Graff, Maud J. L.; Morandi, Alessandro (Specialist in geriatrics and gerontology) (Cham, Switzerland : Springer, 2020)
'This book focuses on evidence-based occupational therapy in the care of older adults in different clinical settings, from home to acute hospital, from intensive care unit to rehabilitation centers and nursing homes. Occupational therapy has progressively developed as a new discipline aiming to improve the daily life of individuals of different ages, from children to older adults. The book first reviews the interaction between occupational therapy and geriatrics and then discusses in depth how occupational therapy interventions are applied in the community, in the acute hospital and in the nursing home. It highlights the key role of occupational therapy in the management of frail patients, including critically ill older patients and persons with dementia, and describes in detail how to maintain occupational therapy interventions across different settings to avoid the fragmentation of care. The ageing population requires new innovative approaches to improve the quality of life, and as such this book provides clinicians with handy, key information on how to implement occupational therapy in the daily clinical care of older adults based on the current scientific evidence'--Publisher's description
Introduction -- Team, occupational therapist and geriatrician -- Occupational therapy in the community -- Occupational therapy in the intensive care unit -- Occupational therapy in rehabilitation settings -- Occupational therapy in nursing home -- Occupational therapy and palliative care -- The present and the future of occupational therapy.
Includes bibliographical references.
Online resource; title from electronic title page (ProQuest Ebook Central, viewed on January 19, 2021).
WorldCat record variable field(s) change: 650
Keywords: Occupational therapy for older people; Aging; Older people; Occupational Therapy -- methods; Aging; Aged; Occupational therapy for older people; Electronic books